Youthful victimization in post-war Bosnia and Herzegovina: A multi-level analysis of a national sample. (November 2022) - Rees, Carter; Winfree, L Thomas
Intra-national conflicts with racial or ethnic elements can complicate post-war reconciliation. From 1992 to 1995, much of the former Yugoslavia, a nation largely drawn from three distinct ethnic groups, was embroiled in such a conflict. After the signing of the Dayton Peace Accord, it was feared that schools would become a surrogate battlefield for school-aged children within the newly created nation of Bosnia and Herzegovina (BiH). Group threat theory and the imbalance of power thesis provide differing views on such conflicts. Group threat theory posits that as a population – in this case a school – approaches maximum ethnic diversity, the residents – in this case the students – will feel increasingly threatened, resulting in higher cross-group victimizations. The imbalance of power thesis suggests that a group's decision to victimize another group depends on the relative lack of ethnic diversity: the extent to which one ethnic group dominates a school, the likelihood of victimization of any smaller groups increases. We explore which of these two theories best explains victimization levels within a sample of 2003 school-aged BiH adolescents born in areas dominated by Muslim Bosnians, Eastern Orthodox Serbians, or Roman Catholic Croatians. We find that there is an ethnic component to victimizations: students born in Serbia face higher levels of victimization than do their Bosnian-born counterparts under conditions that fit better with group threat theory than the imbalance of power thesis. We speculate about the significance of these findings for national ethnic harmony in BiH.